Debutante with a Dangerous Past - Hastings, Samantha (Harlequin historicals., 2023)
"After her criminal father is killed, Miss Nancy Black is forced to seek out her estranged aristocratic grandfather. He offers her a new life as a debutante, but only if she stays out of trouble! Easier said than done when she starts to fall for rebellious Lord Matthew Stringham. Can Nancy risk her heart by telling Matthew the truth about her identity before her dangerous past catches up with her?"--